Food Safety - Bushway, Alfred; Calder, Beth; Bolton, Jason (Maine Policy Review, 2011)
The authors describe the importance of food safety regulations and practices in this era of global food systems and illustrate some of the challenges facing Maine’s small food producers and processors.
Keywords: Maine; food safety